Pengaruh Perilaku Kepemimpinan Terhadap Kinerja Guru Di Sekolah SMP Negeri 3 Satap Bangkurung: The Influence of Leadership Behavior on Teacher Performance at SMP Negeri 3 Satap Bangkurung School - Firmansyah, Andrie; Tandiawan, Vira; ariska; Thaib, Muh (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2024)
This research was conducted to determine and analyze the influence of leadership behavior on teacher performance at the SMP Negeri 3 Satap Bangkurung School. The analytical method used in this research is simple linear regression analysis using 8 samples. Based on the results of data processing with the help of the SPSS version 25 program, a simple linera regression equation was obtained Y = 47,447 + 0.631X. The constant value is 47,447, meaning that if it is not controlled by the leadership behavior variable, the performance will be 47,447, the leadership behavior variable (X) has a significant influence on performance (Y). the correlation coefficient is 0.760 or is in the interval 0.60 – 0.80, meaning that the relationship between the independent variable leadership behavior and the dependent variable performance has a strong relationship. The coefficient of determination (R2) of 0.578 or 57.8% shows the percentage of influence or contribution of the independent variable in explaning the dependent variable, namely 57.8% and the rest is explained by variables other than the variables being tested. The results of the T test show that the leadership behavior variable has a significant effect on performance with a T count of 2.865 and a T table of 2.570.